2020
DOI: 10.1002/cctc.202000224
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Formation of Active Sites on Highly Crystalline Co Branched Nanoparticles for Improved Oxygen Evolution Reaction Electrocatalysis

Abstract: The electrocatalysis of the oxygen evolution reaction (OER) at the surface of oxidized metal electrocatalysts is highly dependent on the structure and composition of the surface oxide. Here, Au core‐ Co branched nanoparticles were synthesized using a cubic‐core hexagonal‐branch growth approach in a slow reductive solution synthesis, resulting in highly crystalline metallic hcp Co branches. Electrochemical surface oxidation of the Co branched nanoparticles resulted in formation of Co(OH)2 that enable the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The formation of branched nanoparticles with two connected components is well known. For example, our group has shown that well-defined branches with dimensions on the tens of nanometers can be grown by carefully selecting a core material that adopts a face-centered cubic (fcc) structure, such as Pd or Au, and a branch material that adopts a hexagonal close-packed (hcp) structure, such as Ru, Co, or Ni (13,(16)(17)(18)(19)(20). In these papers, the hcp branches preferentially grow along the c axis of the crystal structure to form elongated branches directly off the fcc cores.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of branched nanoparticles with two connected components is well known. For example, our group has shown that well-defined branches with dimensions on the tens of nanometers can be grown by carefully selecting a core material that adopts a face-centered cubic (fcc) structure, such as Pd or Au, and a branch material that adopts a hexagonal close-packed (hcp) structure, such as Ru, Co, or Ni (13,(16)(17)(18)(19)(20). In these papers, the hcp branches preferentially grow along the c axis of the crystal structure to form elongated branches directly off the fcc cores.…”
Section: Introductionmentioning
confidence: 99%
“…By deliberately choosing a branch metal that preferentially adopts an hcp structure, such as Ru and Co, and a core that is an fcc metal, bimetallic branched nanoparticles can be synthesized. The versatility of this method has been demonstrated by the well-defined branched nanoparticles formed with different bimetallic combinations, such as Pd-core Ru-branch, , Au-core Ru-branch, Au-core Ni-branch, and Au-core Co-branch, as shown in Figure b–e.…”
Section: What Are the Synthesis Strategies?mentioning
confidence: 97%
“…By deliberately choosing a branch metal that preferentially adopts an hcp structure, such as Ru and Co, and a core that is an fcc metal, bimetallic branched nanoparticles can be synthesized. The versatility of this method has been demonstrated by the well-defined branched nanoparticles formed with different bimetallic combinations, such as Pdcore Ru-branch, 1,24 Au-core Ru-branch, 13 Au-core Ni-branch, 3 and Au-core Co-branch, 40 as shown in Figure 3b−e. Cubic-core hexagonal-branch growth enables catalytically important branched nanoparticle structures to be accessed by hcp materials for the first time, where this was previously dominated by fcc metals.…”
Section: Cubic-core Hexagonal Branch Growth: a Bimetallic Polymorphis...mentioning
confidence: 99%
“…Nanoparticle electrocatalysts have attracted considerable interest for the replacement of bulk noble metal oxide catalysts due to their increased surface area to volume ratio, exposure of more active sites to reduce the amount of material needed to undergo reactions like the OER, [12][13][14] and offering a high degree of physical and chemical property tunability for the modulation of catalytic performance. 15,16 In particular, earth-abundant transition metal (TM)-based nanocatalysts have been reported to have comparable electrochemical performance to noble metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%